2020
DOI: 10.1371/journal.pone.0233905
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics, physiological, and biochemical analysis of cross tolerance mechanisms in response to heat and water stresses in soybean

Abstract: Water stress (WS) and heat stress (HS) have a negative effect on soybean plant growth and crop productivity. Changes in the physiological characteristics, proteome, and specific metabolites investigated on molecular and cellular functions were studied in two soybean cultivars exposed to different heat and water stress conditions independently and in combination. Leaf protein composition was studied using 2-DE and complemented with MALDI TOF mass spectrometry. While the two cultivars displayed genetic variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 85 publications
0
21
0
Order By: Relevance
“…Furthermore, the integration of proteomics data with others from genomics, transcriptomics, or metabolomics provides wider scope in understanding biological processes ( Zhang and Kuster, 2019 ). In soybean, proteome studies on abiotic stress have been reported on flood, drought, heat, and salinity ( Das et al, 2016 ; Ji et al, 2016 ; Yin and Komatsu, 2017 ; Katam et al, 2020 ). A case in point is the integration of metabolome and proteome studies of the maize atg12 mutant which revealed a role for ATG12 in autophagic recycling by proteome remodeling and lipid turnover ( McLoughlin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the integration of proteomics data with others from genomics, transcriptomics, or metabolomics provides wider scope in understanding biological processes ( Zhang and Kuster, 2019 ). In soybean, proteome studies on abiotic stress have been reported on flood, drought, heat, and salinity ( Das et al, 2016 ; Ji et al, 2016 ; Yin and Komatsu, 2017 ; Katam et al, 2020 ). A case in point is the integration of metabolome and proteome studies of the maize atg12 mutant which revealed a role for ATG12 in autophagic recycling by proteome remodeling and lipid turnover ( McLoughlin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…One situation of multiple stress factors that has been receiving attention in studies with is simultaneous water deficit and high temperature, which are almost dependent as it usually occurs at the same time in the field [ 13 ]. In these conditions, soybean was affected with greater intensity when water stress was imposed at higher temperatures [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further, more abundance of proteins related to Calvin cycle, protein synthesis assembly and degradation, defense, and redox homeostasis contributed to better growth and yield in elevated CO 2 was reported (Maurya et al., 2020). In legumes, for example, soybean, proteomics together with physiological and biochemical analysis led to identification of cross‐tolerance mechanisms in response to heat and water stresses (Katam et al., 2020). The study reported elevated activities in antioxidant enzymes, such as increased ascorbate peroxidase enzyme, which restored oxidation levels and sustained soybean plants during stress.…”
Section: Rapidly Evolving Omics Approachesmentioning
confidence: 99%
“…The study reported elevated activities in antioxidant enzymes, such as increased ascorbate peroxidase enzyme, which restored oxidation levels and sustained soybean plants during stress. In addition, proteins such as MED37C, a probable mediator of RNA polymerase transcription II, were elevated in response to combined heat stress and water stress levels (Katam et al., 2020).…”
Section: Rapidly Evolving Omics Approachesmentioning
confidence: 99%